Comparison of Corneal Parameters of Children with Diabetes Mellitus and Healthy Children. (4th November 2019) - Wang, Shanshan; Jia, Yan; Li, Tao; Wang, Anken; Gao, Lu; Yang, Chenhao; Zou, Haidong
Abstract : Purpose . To compare differences in central corneal thickness (CCT), corneal curvature, and other corneal measurements of children with diabetes mellitus (DM) and healthy children, and to investigate related factors. Methods . This was a case-control study. From January to February 2018, 50 children with diabetes mellitus were selected as a case group, and 46 healthy children and adolescents without diabetes mellitus were selected as a control group. Corneal topography and CCT were analyzed using a corneal topography measuring apparatus and biometrics (IOL Master). In the diabetic group, we analyzed whether age, course of disease, sex, glycosylated hemoglobin, triglyceride level, total cholesterol, body mass index (BMI), parental BMI, birth history, feeding history, pregnancy, or puerperal history were related to corneal morphology. Results . There was a significant difference in CCT between groups, but no significant differences were found in corneal diameter, corneal curvature R1 or R2, or corneal topography. Central corneal thickness was not correlated with other clinical factors in the diabetes group. Conclusion . Early screening and close follow-up of keratopathy in children with diabetes are imperative.